Analisis Yuridis Surat Edaran Dalam Sistem Hukum Indonesia Konsistensi Materi Muatan Surat Edaran Penanganan Covid-19 (International Forum of Researchers and Lecturers, 2023)
The rapid response to COVID-19 by central and local governments relies on Circular Letters, convenient policy tools requiring no external approval. Despite their ease of use, Circular Letters often trigger debates and legal disputes due to inconsistencies in content and legal status.The research methodology employed is normative legal research, conducted by examining library materials or secondary data. The findings of the study reveal that the existence of Circular Letters, which is a form of policy regulation, results from the discretionary power vested in the government. However, as discussed above, there is a lack of consistency among officials regarding the format and content of Circular Letters, leading to some Circular Letters containing legal norms that are generally binding on the public. In contrast, according to the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 80 of 2012 and the Regulation of the Head of the National Archives of the Republic of Indonesia No. 2 of 2014, Circular Letters are classified as administrative document products. Consequently, the implication of this research is that Circular Letters should only serve as internal communication tools, providing notifications within the internal organizational structure.